COVID-19 Vaccine Booster Dose Fails to Enhance Antibody Response to Omicron Variant in Reinfected Healthcare Workers - Leire Fernández-Ciriza; Álvaro González; José Luis del Pozo; Alejandro Fernandez-Montero; Francisco Carmona-Torre; Paula Martínez de Aguirre; María del Mar Sarasa; Silvia Carlos; Gabriel Reina (Viruses)
The emergence of new variants and diverse vaccination regimens have raised uncertainty about vaccine effectiveness against SARS-CoV-2. This study aims to investigate the impact of Omicron primo-/reinfection and primary vaccination schedules on the immunogenicity of an mRNA-based booster dose over a six-month period. We conducted a prospective cohort study to assess the durability and level of antibodies of 678 healthcare workers fully vaccinated against COVID-19. They were categorized based on their primary vaccination regimen. Blood samples were collected before the booster dose and 1 and 6 months after. Significant Anti-S-RBD differences were found between previously infected and naïve volunteers (p = 0.01). Considering the initial vaccine schedules, mRNA-based vaccines displayed significant higher antibody production and longer persistence among both infected and naïve participants. After the booster dose, participants primoinfected with the Omicron variant exhibited higher antibody concentrations than those who experienced reinfection, even after 6 months of follow-up (22,545 and 9460 U/mL, respectively). Moreover, these groups showed the most pronounced disparity in antibody titers ratios between infected and uninfected individuals. Overall, the booster dose failed to enhance humoral response in individuals reinfected with the Omicron variant after receiving it. Hybrid immunity and mRNA-based vaccine initial schedules showed higher levels and longer persistence of antibodies.